2022
DOI: 10.1371/journal.pone.0262806
|View full text |Cite
|
Sign up to set email alerts
|

The adult microbiome of healthy and otitis patients: Definition of the core healthy and diseased ear microbiomes

Abstract: Otitis media (OM) and externa (OE) are painful, recurrent ear conditions. As most otitis publications focus on the bacterial content of childhood ears, there remains a dearth of information regarding the adult ear microbiome including both bacteria and fungi. This study compares the outer ear microbiome of healthy adults to adults affected by OE and OM using both intergenic-transcribed-spacer (ITS) and 16S-rDNA sequencing. The adult ear core microbiome consists of the prokaryote Cutibacterium acnes and the euk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Indeed, it has been shown that the healthy ear core microbiome includes Staphylococcus capitis and S. capitis/caprae, while the diseased ear core is composed of known bacterial and fungal pathogens, such as Aspergillus sp., Candida sp., Pseudomonas aeruginosa, S. aureus, and Corynebacterium jeikeium. This awareness underscores the importance of targeting therapies not only to eliminate pathogens, but also to restore a healthy microbiome in order to improve treatment outcome and limit inappropriate antibacterial treatments, thereby improving overall antimicrobial stewardship [20]. The higher incidence of OE found in the summer months also highlights the importance of the ear microbiome.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it has been shown that the healthy ear core microbiome includes Staphylococcus capitis and S. capitis/caprae, while the diseased ear core is composed of known bacterial and fungal pathogens, such as Aspergillus sp., Candida sp., Pseudomonas aeruginosa, S. aureus, and Corynebacterium jeikeium. This awareness underscores the importance of targeting therapies not only to eliminate pathogens, but also to restore a healthy microbiome in order to improve treatment outcome and limit inappropriate antibacterial treatments, thereby improving overall antimicrobial stewardship [20]. The higher incidence of OE found in the summer months also highlights the importance of the ear microbiome.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, also beta-diversity such as PCoA indicated differences in microbial composition between the otitis externa and control groups. In a study, alpha diversity did not differ significantly between the otitis externa and healthy control groups [ 21 ]. However, in several previous studies, decreased microbiome diversity was reported in inflammatory and infectious diseases [ 22 , 23 ], and changes in microbiome composition compared to normal skin were reported in skin diseases such as atopic dermatitis [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus warneri , a distinct taxon at the species level, is a catalase-positive, oxidase- and coagulase-negative skin commensal that constitutes <1% of the skin Staphylococcus population [ 29 ]. Although it is a rare cause of infection, Staphylococcus warneri was the sixth most frequently isolated Staphylococcus species in acute otitis externa [ 21 ]. Therefore, the commensals Pseudomonas and Staphylococcus warneri, as pathogens in the ear canal, may affect the epithelial barrier and innate immunity, play a role as pathogens under the environment of changes in the composition of the microbiome of the ear canal.…”
Section: Discussionmentioning
confidence: 99%
“…A sample-specific DNA extraction procedure with the possibility of its validation is recommended ( Tiew et al, 2020 ). A wide range of ready-to-use techniques have been applied; for instance, the ZymoBIOMICS DNA Kit (Zymo Research, United States) was successfully used for human swab samples ( Burton et al, 2022 ) and InviMag stool DNA kit (Stratec Molecular, Germany) preceded by mechanical and chemical cell lysis were adopted for breast milk samples ( Boix-Amorós et al, 2019 ).…”
Section: Methodologies and Challenges In Neonatal Mycobiome Studiesmentioning
confidence: 99%